A real-time recombinase polymerase amplification assay for the rapid detection of Vibrio harveyi. (April 2019) - Pang, Jianhu; Wang, Qiong; Fei, Yuejun; Zhu, Peng; Qiao, Longliang; Huang, Hailong; Dang, Chenyang; Gao, Weifang
Abstract: Vibrio harveyi is a pathogen that infects fish and shellfish worldwide, causing severe economic losses for the aquaculture industry. As the early diagnosis of V. harveyi infection is crucial to disease surveillance and prevention in cultured marine animals, a fast and accurate method to detect V. harveyi is required. Here, we performed recombinase polymerase amplification (RPA) using novel primers specifically designed to recognize the V. harveyi toxR gene, which encodes a transmembrane protein, and then hybridized this gene with a carboxy fluorescein (FAM)-labeled probe. The optimal conditions for the real-time RPA assay were a probe concentration of 90 nM and a 20 min incubation at 37 °C. The sensitivity of our real-time RPA assay was 50 copies of the standard plasmid, while that of real-time PCR was 500 copies. In V. harveyi -spiked Pseudosciaena crocea samples, the sensitivity of our real-time RPA was 60 CFUs per reaction, while that of PCR was 600 CFUs per reaction. SPSS probit regression analysis indicated that the limit of detection (LOD) of our RPA assay, with 95% probability, was 18 copies. The LOD was reached within 20 min and was highly reproducible across eight independent assays. Our novel RPA method successfully differentiated V. harveyi from all other tested Vibrio species, including some that were closely related. Our real-time RPA assay, in combination with a rapid DNA extraction protocol, is a fast and accurate tool for the detection of V. harveyi and for monitoring disease outbreaks. This tool will be valuable for the aquaculture industry. Highlights: Real-time RPA was developed first time to detect V. harveyi. The developed RPA assays provide a rapid, simple, sensitive and specific alternative tool for detection of V. harveyi. This novel real-time RPA assay is an accurate tool for point-of-care testing of V. harveyi in aquaculture.